Hubungan dalam Pekerjaan dan Stres Kerja Staf Engineering - Alya Azzahra Utomo; Rizki Amalia; Terry Y.R. Pristya; Nayla Kamilia Fithri (FORIKES, 2022)
Workers still have to travel and fulfill their responsibilities at work despite the COVID-19 outbreak. The workforce often faces difficult working conditions due to the COVID-19 outbreak. The purpose of this study was to analyze the correlation between the relationship at work with the job stress of engineering staff. The design of this study was cross-sectional. The sample size was based on the two-proportion difference hypothesis test formula (62 staff), but was increased to 66 staff. Data were collected using a questionnaire as an instrument. The data that has been collected was analyzed using the Chi-Square test. The results of the analysis show that there is a correlation between the relationship at work (p=0.014) and work stress. Therefore, it is necessary to improve communication between staff, the spirit of mutual assistance, and mutual recreation in order to improve relations at work.Keywords: relationship in work; work stress; fabrication company ABSTRAK Para pekerja masih harus bepergian dan memenuhi tanggung jawabnya di tempat kerja meskipun wabah COVID-19 masih melanda. Tenaga kerja sering menghadapi kondisi kerja yang menyulitkan akibat wabah COVID-19. Tujuan penelitian ini adalah untuk menganalisis korelasi antara hubungan dalam pekerjaan dengan stres kerja staf engineering. Rancangan penelitian ini adalah cross-sectional. Ukuran sampel didasarkan pada formula uji hipotesis perbedaan dua proporsi (62 staf), namun ditambah menjadi 66 staf. Data dikumpulkan menggunakan kuesioner sebagai instrumen. Data yang telah terkumpul dianalisis menggunakan uji Chi-Square. Hasil analisis menunjukkan bahwa ada korelasi antara hubungan dalam pekerjaan (p=0,014) dengan stres kerja. Oleh karena itu perlu ditingkatkan komunikasi antar staf, semangat saling membantu, dan rekreasi bersama agar dapat memperbaiki hubungan dalam pekerjaan.Kata kunci: hubungan dalam pekerjaan; stres kerja; perusahaan fabrikasi